Affective Reactions of Vietnamese Toward Coworkers With Disabilities and Perceptions of Community Inclusion. (October 2019) - Hsu, Tsu-Hsuan; Chao, Pei-Ju; Huang, Ying-Ting; Bezyak, Jill L.; Ososkie, Joseph N.
Vietnam is in the emerging stage in supporting and protecting people with disabilities (PWDs) in terms of employment rights and opportunities. The main purpose of this study was to explore how Vietnamese perceive their coworkers with disabilities in general workplace settings. In addition, the secondary objective of this study was to explore how Vietnamese perceive community acceptance and inclusive education of PWDs in different environmental contexts. Results indicated participants had generally positive affective reactions toward their coworkers with disabilities in the workplace. However, findings also indicated that Vietnamese people possessed hierarchical attitudes toward people with different types of disabilities in terms of community acceptance and educational rights.